Emergency surgery for a patient with a thoracic spinal epidural abscess: a case report and literature review - Sanbiao Li; Shengqian Mei; Libin Huang; Junhui Liu; Yilei Chen; Bao Huang; Fengdong Zhao (Journal of International Medical Research, 2023)
A man in his early 40s visited the Emergency Department because of no motor function in his lower limbs for 10 hours. Magnetic resonance imaging of his thoracic spine showed that the thoracic spinal canal (T2–T6) was occupied, and the thoracic spinal cord was compressed. In view of the severe symptoms, we quickly completed preoperative preparations and performed a thoracic laminectomy within 24 hours of paralysis of both lower limbs. Postoperatively, the patient underwent rehabilitation exercise. Four weeks later, the patient’s lower limbs had full 5/5 strength. We reviewed the related literature to summarize the clinical guidelines with spinal surgeons. Timely diagnosis of thoracic spinal epidural abscess, early surgical treatment, and anti-infection management and rehabilitation exercise are essential for the full recovery of lower limb muscle strength.